Endoscopic endonasal anatomical study of the cavernous sinus segment of the ophthalmic nerve. (25th November 2014) - Dolci, Ricardo L. L.; Carrau, Ricardo L.; Buohliqah, Lamia; Zoli, Matteo; Mesquita Filho, Paulo M.; Lazarini, Paulo R.; Ditzel Filho, Leo F. S.; Prevedello, Daniel M.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis This cadaveric study analyzes the endoscopic endonasal anatomy of the ophthalmic division of the trigeminal nerve (V1), from the middle fossa to its orbital entry via the superior orbital fissure. Anatomical relationships with the surrounding cranial nerves and blood vessels are described, with emphasis on their clinical correlation during surgery in this region. Our objective was to describe the anatomical relationships of the ophthalmic division of the trigeminal nerve. Study Design Cadaveric study. Methods Thirty middle cranial fossae, in adult human cadaveric specimens, were dissected endonasally under direct endoscopic visualization. During the dissection, we noted the relationships of the V1 nerve with the other trigeminal branches, as well as with the oculomotor and trochlear nerves, the paraclival and cavernous portions of the internal carotid artery, and the superior orbital fissure (SOF). Results The V1 nerve is the most superior trigeminal branch and runs upward and obliquely, along the middle portion of the lateral wall of the cavernous sinus. The V1 nerve joins the oculomotor and trochlear nerves to exit the cavernous sinus and enter the orbit through the SOF. Ten percent of the specimens displayed the trochlear nerve running along as a mate of the V1 nerve. The V1 nerve borders two key triangles in the lateral wall of the cavernous sinus, and the Parkinson's and anteromedial triangles. Conclusions In this study, the V1 nerve was a constant and reliable landmark, thus allowing the identification of the anteromedial triangle. This potential space can serve as an adequate window to access the temporal lobe. Knowledge of this anatomy is essential when planning and executing endonasal surgery in this region. Level of Evidence NA Laryngoscope, 125:1284–1290, 2015